Radiographic Prescription Trends among Palestinian Dentists for Dental Implant Placement - A Cross Sectional Survey - Hakam Rabi; Emad Qirresh; Tarek Rabi (Journal of Dental Problems and Solutions - Peertechz Publications, 2017)
Background: In this present era implant dentistry has seen exponential growth and its success mainly depends upon a proper treatment planning and its execution. Radiographic imaging has a pivotal role in the planning of implant placement and follow up of implant survival. The Context and Purpose of the Study: To study the radiographic prescription trends for dental implants among Palestinian dental practitioners. A sample of 150 dentists chosen at random in a dental conference received a questionnaire. Results: 114 dentists returned full questionnaires. It was observed that the majority of the surveyed dentists prescribe panoramic radiographs for dental implant assessment based on its availability. The motivating factors for prescribing the specifi c radiologic examination was Availability (42.99%), availability + cost(17.53%), Cost + Measurement precision(3.51%), Cost + Radiation Dose(10.53%), Measurement precision(25.44%). Conclusions: The majority of surveyed dentists prescribe panoramic radiographs for dental implant assessment based on its availability and only a small number strictly adhered to the recommended guidelines of the international associations with regards to cross sectional imaging.